INTEGRATED ASSESSMENT OF INVESTMENT ATTRACTIVENESS OF REGIONS IN UKRAINE - KYSHAKEVCYH, BOHDAN; NAKHAEVA, MARYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article proposes a model for the integral assessment of the investment attractiveness of the regions in Ukraine, taking into account seven blocks of their socio-economic development: economic development, investment activity, financial self-sufficiency, labor market and entrepreneurship, infrastructure, socio-economic development, the effectiveness of regional investment policy. The article substantiates the need to take into account the effectiveness of regional investment policy when assessing investment attractiveness and the feasibility of differentiating such assessments depending on the type of investor and the type of investment. The authors propose to take into account such features of the investment process by using DEA-analysis and selection of appropriate weight coefficients that determine the share of each block of indicators regarding socio-economic development of regions in their overall investment attractiveness. Since the VRS assumption or BCC model in DEA analysis provides for a change in efficiency in accordance with a change in the scale of operations, to assess the effectiveness of regional investment policy, we further used the CRS assumption about the constancy of the scale of operations, since the size of investment flows in the Ukrainian economy is still relatively small. As a result, Kiev, Dnepropetrovsk and Kiev regions turned out to be the most attractive for both long-term and short-term investments. The Kherson region turned out to be the least attractive for long-term investments. In the case of short-term investments, the Sumy region showed the lowest value of the integral indicator of investment attractiveness. Some regions showed a significant difference in the value of the integral indicator of investment attractiveness for short and long-term investments, that once again emphasizes the importance of the initial stage of assessing the investment attractiveness of the region, namely, identifying the type of investor, his goals and investment period.
Keywords: investment attractiveness; investment climate; integrated assessment; effectiveness of regional investment policy; DEA analysis